The Role of Theory in Folkloristics and Comparative Religion - Kamppinen, Matti (Approaching religion, 2014)
Lauri Honko (1932-2002), the Finnish professor of folkloristics and comparative religion was a prolific and multi-talented researcher, whose topics of research ranged from the study of folk beliefs, folk medicine and Ingrian laments to the general theories of culture, identity and meaning. Honko studied Finno-Ugric mythologies, Karelian and Tanzanian folk healing, and South Indian oral traditions. Lauri Honko was known for his originality and theoretical innovations: he constructed multiple approaches to the study of culture that are still relevant in folkloristics and comparative religion.In this paper I aim at explicating and analysing Honko’s views about the roles of theory in folkloristics and comparative religion. More precisely, I will cover two themes. First, I will look at how Honko constructed and utilised theories during the different stages of his career. Second, I will explicate one of the central elements underlying Honko’s theory of culture, namely, functionalism, which provided the framework for his innovations such as the ecology of tradition and folklore process, and for conceptual constructs such as the ‘pool of tradition’ and ‘systems of culture’. I will conclude by assessing the future relevance of Honko’s theories in folkoristics and comparative religion.